2005
DOI: 10.1161/circulationaha.105.554832
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery of Damaged Skeletal Muscle Through Synchronized Vasculogenesis, Myogenesis, and Neurogenesis by Muscle-Derived Stem Cells

Abstract: Background-Recent studies have shown that skeletal muscle-derived stem cells (MDSCs) can give rise to several cell lineages after transplantation. However, the potential therapeutic uses of MDSCs, the functional significance of the transplanted tissue, and vasculogenesis, myogenesis, and reconstitution of other tissues have yet to be investigated in detail. In addition, the relationship between MDSCs and mesenchymal bone marrow cells is of interest. Methods and Results-We developed a severe-damage model of mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
169
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(190 citation statements)
references
References 27 publications
18
169
2
1
Order By: Relevance
“…Given the presence of resident stem and SCs within the skeletal muscle tissue, native tissue skeletal muscle-derived MSCs (MDSCs) would appear as the favorite source for regeneration therapies [34]. In response to muscle damage, the SCs population is activated by the released biomolecules and begins to proliferate and originates large numbers of muscle progenitor cells (MPCs), which will in turn contribute to skeletal muscle structure reconstruction.…”
Section: Mscs' Sources For Skeletal Muscle Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the presence of resident stem and SCs within the skeletal muscle tissue, native tissue skeletal muscle-derived MSCs (MDSCs) would appear as the favorite source for regeneration therapies [34]. In response to muscle damage, the SCs population is activated by the released biomolecules and begins to proliferate and originates large numbers of muscle progenitor cells (MPCs), which will in turn contribute to skeletal muscle structure reconstruction.…”
Section: Mscs' Sources For Skeletal Muscle Regenerationmentioning
confidence: 99%
“…The expansion of MDSCs is possible, but as it has long been known, it leads to dedifferentiation of early committed myogenic cells [40] and loss of potential. As little as 1 day in culture following isolation and sorting hinders its engraftment potential and contribution to regeneration events, hence turning it difficult to attain relevant cell numbers for implantation [34]. Confirming this loss of potential, the implantation of freshly isolated SCs in numbers as low as 250 cells outperforms the use of as many as 1.5 × 10 5 MPCs of first passage derived from SCs expansion [35].…”
Section: Mscs' Sources For Skeletal Muscle Regenerationmentioning
confidence: 99%
“…Stem cell therapy may potentially overcome these issues and be a major focus in the future for the management of a broad range of muscular dystrophies. Recent studies demonstrated that bone marrow stromal cells (Dezawa et al 2005) or muscle-derived stem cells (Tamaki et al 2005) are able to generate muscle cells and can repair muscle degeneration in vivo. Reconstitution of the healthy gene into such stem cells prepared from the patients and their retransplantation might be a new potential strategy to treat muscular dystrophies.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…They are also positive for myogenic markers, including desmin and Myo-D. On the contrary, MDSCs do not express hematopoietic stem cells and other blood lineage markers, such as c-Kit, CD45, CD3, CD4, CD5, CD8, and CD14 [28,38]. Reports pertaining to the production of CD34 differ: some authors have confirmed its production, while other authors consider MDSCs as CD34 negative cells [28,39,40]. It has been experimentally shown that MDSCs cultured in medium with a low serum concentration spontaneously differentiate into myotubes [37].…”
Section: Multipotent Muscle-derived Stem Cellsmentioning
confidence: 99%